IMPLEMENTASI METODE PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR MATA PELAJARAN SISTEM KELISTRIKAN DI KELAS XII TEKNIK KENDARAAN RINGAN SMK MUHAMMADIYAH PAKEM TAHUN PELAJARAN 2016/2017 - Adhi Catur Prabowo; Subagyo Subagyo (Jurnal Taman Vokasi, 2016)
This study aimed to imrpove: (1) learning interest and (2) learning achivement of ignition system by using jigsaw. The type of this study was a classroom action research. The research subject was the eleventh grade students of class XII D of SMK Muhammadiyah Pakem in academic year 2016/2017 consisted of 31 students. The research object was learning interest and learning achivement of ignition system. Data collection techniques used questionaire and test. The research instruments wete leson plan, questionaire,Â  test, and observation guideline. Data analysis techniques used descriptive analysis and quantitative analysis to know the pecentage of learning interest and learning achivement of ignition system. This study shows that (1) the use of jigsaw could improve learning interest of ignition system. The score of learning interest in cycle I was 40.093 in low category improved in cycle II became 51.742 in fair category and improved again in cycle III became 58.419 in high category. (2) The use of jigsaw could improve learning achivement of ignition system. The score of learning achivement of ignition system in pre cycle was 52.74, cycle I was 65.81, cycle II was 74.19, and cycle III was 79.35. The students who were completed in learning in cycle I was 5 students (16.13%), cycle II was 23 tudents (74.19%), dan cycle III was 29 studentes (93.55%).